Coatings for Ti6Al4V in cryogenic space engine applications. (2nd February 2010) - Lemaire-Caron, I.; Isac, N.; Quillien, M.; Da Silva Botelho, T.; Gras, R.; Ganne, T.
Fretting damage appears in quasi-static mechanisms submitted to small amplitude oscillatory motion. Depending on the amplitude of displacement, it could lead to catastrophic failure in many industrial applications due to crack initiation or wear damage. To reduce the damage caused by fretting, an increasing use of coatings and surface treatments has been made. In service, the grooves in cryogenic (liquid hydrogen) turbopump shaft in Ti6Al4V can be damaged, a Cu-Ni-Si P.V.D. coating has solved the problem. New diamond-like-carbon (DLC) coatings with interesting tribological properties seem to be attractive for solving industrial problems. The present study analyses the behaviour of plasma nitrided Ti6Al4V with or without a DLC layer. Its effect on crack initiation resistance will be characterised for TI6Al4V substrate. The increase of load capacity due to the treatments will be evaluated in a cryogenic environment.